Relationship between Adolescent Athletes’ Values and Behavior in Sport and Perceived Coach’s Character Development Competency (Baltic Journal of Sport and Health Sciences, 2013)
Research  background  and  hypothesis.  This  study  examined  the  relations  between  reported  youth  athletes’ prosocial  and  antisocial  behavior  and  personal  and  social  factors  in  sport  context  and  whether  these  variables  accounted for age and sports experience differences in reported behaviors values in sport and perceptions of coach’s  character development competency. The aim of the research was to determine age and sports experience differences in manifestation of youth athletes’ values in sport, perceived coach’s character development competency and behaviors that occur in sport, and to examine interrelations between these variables. Research methods. The sample included 201 athletes recruited from Kaunas and Alytus sports schools. The participants  completed  the Youth  Sport Value  Questionnaire-2  (YSVQ-2  -  Lee  et  al.,  2008),  the  Prosocial  and Antisocial Behavior in Sport Scale (PABSS – Kavussanu, Boardley, 2009), and adapted version of the Coaching Efficacy Scale (CES– Feltz et al., 1999).Research results. The positive correlation between values in sport, perceived coach’s character development  competency  and  prosocial  behavior  of  athletes  were  established.  These  values  also  had  negative  correlations  with  antisocial  behavior  whereas  status  values  correlated  negatively  with  prosocial  behavior.  Coach’s  character  development competency was perceived stronger by younger athletes (p < 0.05). Competence values were more  important to these athletes compared to older ones (p < 0.05).  Discussion and conclusions. Research revealed the importance of moral and competence values for adolescent  athlete’s moral behavior in sport. Perceived character-development effectiveness positively correlated with athletes’  prosocial behavior; however, it was unrelated to antisocial behavior. Thus, perceiving the coach as being effective in  instilling an attitude of good moral character may lead to an increased frequency of desirable behaviors but does not  appear to have any effect on antisocial conduct. It was found that athletes’ prosocial acts were more frequent than antisocial ones, however, more experienced athletes displayed more frequent antisocial behavior to the teammates.  These findings are consistent with the previous presumption that low frequency of engagement in antisocial behaviors   does not necessarily mean that one frequently engages in prosocial action, or vice versa.Keywords:  sport, athletes’ moral behavior, values in sport, perceptions, coaching effectiveness.